Daniel Aguirre-Oteiza. This Ghostly Poetry: History and Memory of Exiled Spanish Republican Poets. U of Toronto P, 2020. - Paul Cahill (Studies in 20th & 21st Century Literature, 2022)
Review of Daniel Aguirre-Oteiza, This Ghostly Poetry: History and Memory of Exiled Spanish Republican Poets. U of Toronto P, 2020. xii + 369 pp.
Keywords: Spanish Poetry; Exile; Memory; Juan Ramón Jiménez; Luis Cernuda; Max Aub; Tomás Segovia; Antonio Machado